Crafting Language for Culinary Excellence: Customizing ESP Content to Align with Student and Industry Needs - Simanjuntak, Khairun Nisa; Ratmanida (VELES Voices of English Language Education Society, 2024)
The alignment of English for Specific Purposes (ESP) materials with the needs of students and the culinary industry is crucial for preparing graduates to excel in the competitive fields of tourism and hospitality. In particular, essential English language skills such as culinary terminology, effective communication in professional kitchen environments, and writing recipes or menus in English should be addressed more in existing curricula. This study aimed to assess the relevance and practicality of current ESP materials within the context of culinary education at an Indonesian university. Using a qualitative descriptive approach, the research involved 40 second-semester students who had completed a course in Professional English, along with 11 waitstaff from hotels and restaurants in West and North Sumatra. The findings revealed significant gaps in the current materials, particularly in areas critical for international customer service and multicultural teamwork, such as food presentation, customer interaction, and sanitation practices. The study concludes that English learning materials must be tailored to meet the general needs of English learners and the specialized demands of the culinary industry. Incorporating relevant terminology, practical communication skills and industry-specific content is essential for better preparing students for professional roles in catering and hospitality. The research suggests that focused classroom techniques on communication and specialized vocabulary can guide educators in developing more effective ESP materials for the culinary field.